2020
DOI: 10.1186/s12302-020-00420-8
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation between concentration of iron oxides and particulate matter in atmospheric dust: case study at industrial site during smoggy period

Abstract: Background Environmental magnetism, focusing on ferrimagnetic iron oxides, provides useful additional information on pollution of different environments. Magnetic methods have been applied to studies of atmospheric dust, namely PM10 (particulate matter smaller than 10 µm) in, e.g., industrial or urban areas. Until now, positive correlation was reported between concentration of iron oxides (expressed in terms of either magnetic susceptibility, saturation remanent or saturation induced magnetizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…This fine magnetic fraction comprises the ubiquitous anthropogenic magnetite and adsorbed potentially toxic elements (PTE), which may cause genotoxic and mutagenic impacts. Several studies proved a relationship between PTE and magnetic parameters in soils [9], sediments [10,11], biomonitors [12][13][14], and atmospheric dust [15][16][17]. This association between the AMP and PTE in magnetic fractions of PM generated from industrial or vehicle emission was shown by [18][19][20].…”
Section: Introductionmentioning
confidence: 89%
“…This fine magnetic fraction comprises the ubiquitous anthropogenic magnetite and adsorbed potentially toxic elements (PTE), which may cause genotoxic and mutagenic impacts. Several studies proved a relationship between PTE and magnetic parameters in soils [9], sediments [10,11], biomonitors [12][13][14], and atmospheric dust [15][16][17]. This association between the AMP and PTE in magnetic fractions of PM generated from industrial or vehicle emission was shown by [18][19][20].…”
Section: Introductionmentioning
confidence: 89%
“…The successful use of magnetic monitoring for soil contamination in industrial areas led to the adoption of magnetic methods for monitoring air pollution in urban environments. A significant contribution of Fe-rich particles to urban dust was clearly demonstrated by detailed studies of PM collected by municipal monitoring networks (e.g., Muxworthy et al 2003 ; Sagnotti et al 2006 ; Górka-Kostrubiec et al 2012 ; Mantovani et al 2018 ; and Petrovský et al 2020 ). Contrary to studies reporting a positive correlation between the concentration of ferrimagnetic iron oxides and particulate matter, Petrovský et al ( 2020 ) reveal a negative correlation between the concentration of PM and saturation induced magnetization.…”
Section: Introductionmentioning
confidence: 98%
“…A significant contribution of Fe-rich particles to urban dust was clearly demonstrated by detailed studies of PM collected by municipal monitoring networks (e.g., Muxworthy et al 2003 ; Sagnotti et al 2006 ; Górka-Kostrubiec et al 2012 ; Mantovani et al 2018 ; and Petrovský et al 2020 ). Contrary to studies reporting a positive correlation between the concentration of ferrimagnetic iron oxides and particulate matter, Petrovský et al ( 2020 ) reveal a negative correlation between the concentration of PM and saturation induced magnetization. It is crucial to note that magnetic monitoring is site-specific and predominantly reflects local factors such as the nature of emission sources and weather conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…35,36 Industrial processes such as steelmaking and Fenton-like wastewater treatment inevitably release Fe 2 O 3 particles into the atmosphere. [37][38][39] Previous studies have found that it can promote the heterogeneous reaction of SO 2 through a REDOX process during the conversion between Fe 2+ and Fe 3+ , allowing SO 2 oxidation to SO 4 2− even under dark conditions. 40 In addition, it has been found that the dissolution of Fe 2 O 3 particles can be induced with the addition of oxalic acid.…”
Section: Introductionmentioning
confidence: 99%